Phylogenetic analysis of haemaglutinin gene of avian influenza virus isolate VRI1803/04 - Zulkifli, Hazalina; Ideris, Aini; Omar, Abdul Rahman; Syed Hassan, Sharifah (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
An isolate of avian influenza virus (AIV) designated as VRI1803/04 obtained from Veterinary Research Institute, Ipoh, Perak was used for identification and characterisation using the conventional one step reverse transcription polymerase chain reaction (RT-PCR). Total RNA of the virus was obtained from allantoic fluid of specific-pathogen-free (SPF) embryonated chicken eggs extracted using conventional method. The complete sequence of H3 gene (1701 bp) of VRI1803/04 was determined. The H gene has 89% homology to H3 gene from A/duck/Ukraine/1/63 (H3N8).